Air humidity thresholds trigger active moss spore release to extend dispersal in space and time. (19th December 2015) - Johansson, Victor; Lönnell, Niklas; Rannik, Üllar; Sundberg, Sebastian; Hylander, Kristoffer
Summary: Understanding the complete dispersal process is important for making realistic predictions of species distributions, but mechanisms for diaspore release in wind‐dispersed species are often unknown. However, diaspore release under conditions that increase the probability of longer dispersal distances and mechanisms that extend dispersal events in time may have evolutionary advantages. We quantified air humidity thresholds regulating spore release in the moss Brachythecium rutabulum . We also investigated the prevailing micrometeorological conditions when these thresholds occur in nature and how they affect dispersal distances up to 100 m, using a mechanistic dispersal model. We show that moss spores were mainly released when the peristome teeth were opening, as relative air humidity (RH) decreased from high values to relatively low (mainly between 90% and 75% RH). This most often occurred in the morning, when wind speeds were relatively low. Surprisingly, the model predicted that an equally high proportion of the spores would travel distances beyond 100 m (horizontally) when released in the wind conditions prevailing during events of RH decrease in the morning, that lead to peristome opening, as in the highest wind speeds. Moreover, a higher proportion of the spores reached high altitudes when released at the lower wind speeds during the morning compared to the higher speeds later in the day, indicating a possibility for extended dispersal distances when released in the morning. Dispersal in the morning is enhanced by a combination of a more unstable atmospheric surface layer that promotes vertical dispersal, and a lower wind speed that decreases the spore deposition probability onto the ground, compared to later in the day. Our study demonstrates an active spore release mechanism in response to diurnally changing air humidity. The mechanism may promote longer dispersal distances, because of enhanced vertical dispersal and because spores being released in the morning have more time to travel before the wind calms down at night. The mechanism also leads to a prolonged dispersal period over the season, which may be viewed as a risk spreading in time that ultimately also leads to a higher diversity of establishment conditions, dispersal distances and directions. Abstract : Lay Summary